Desarrollo de un sistema de información móvil para la gestión de ventas en la empresa inversiones la cruz de Trujillo. - Vega Dávila, Wanderley (2018)
This research project "Development of a Mobile Information System on Android for Sales Management in the Investment Company La Cruz de Trujillo". Its objectives are to develop a computer application to facilitate access to information at any time and place, thus increasing the interaction of customers with the company, seeking to improve the recruitment, retention and satisfaction of customers with the business. For the development of the mobile application, the Development IDE of Android Studio was used, since it seeks to implement a native Mobile application to maintain a better user experience, obtaining the maximum performance of the device, and having constant automatic updates. The Visual Studio Development IDE with programming language C # .NET was used for the development of Services WCF with so-called SOAP format, in order to provide greater security and reliability for the exchange of data. In the development of the research, the agile SCRUM development methodology is applied, as it is a collaborative and flexible methodology for managing software development, based on first constructing the highest value functionality for the client, taking into account the principles of continuous inspection.